1993
DOI: 10.1093/brain/116.6.1575
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the role of internal cues in the pathogenesis of parkinsonian hypokinesia

Abstract: Our animal studies suggest that the basal ganglia provide an internal non-specific cue to trigger movement and imply that Parkinson's disease involves a deficiency in this cueing mechanism. Indeed parkinsonian patients typically rely upon external visual cues. To assess the effects of such non-specific cueing mechanisms on movement, we examined patients' utilization of a variety of auditory cues. Ten patients suffering from Parkinson's disease, and their matched controls, pressed buttons at a series of two-way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
119
0
8

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(138 citation statements)
references
References 0 publications
11
119
0
8
Order By: Relevance
“…Second, the inconsistency may be due to the explicit vs implicit nature of the sequencing of movements that the patients had to execute. In the other studies, patients with PD acquired declarative knowledge of the sequence of movements they had to perform because (1) they were asked either to memorize the sequence (Rafal, Inhoff, Friedman, & Bernstein, 1987;Stelmach et al, 1987) or to practice it before the experimental testing began (Benecke et al, 1987;Georgiou et al, 1994;Georgiou, Bradshaw, Phillips, Bradshaw, & Chiu, 1995;Georgiou, Iansek, Bradshaw, Phillips, Mattingley, & Bradshaw, 1993;Jones, Phillips, Bradshaw, Iansek, & Bradshaw, 1992;Rafal et al, 1987) or (2) they were allowed to refer to a written version of the sequence they had to produce at all times during the experiment (Harrington & Haaland, 1991). In this study, however, the subjects were unaware that the triads in the Practiced condition were made of the consecutive juxtaposition of the simple figures they had practiced in Phase III, nor that the triads in the Unpracticed condition were composed of novel simple figures that they had never traced individually before.…”
Section: Mirror-tracing Task: Integration Of Practiced Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the inconsistency may be due to the explicit vs implicit nature of the sequencing of movements that the patients had to execute. In the other studies, patients with PD acquired declarative knowledge of the sequence of movements they had to perform because (1) they were asked either to memorize the sequence (Rafal, Inhoff, Friedman, & Bernstein, 1987;Stelmach et al, 1987) or to practice it before the experimental testing began (Benecke et al, 1987;Georgiou et al, 1994;Georgiou, Bradshaw, Phillips, Bradshaw, & Chiu, 1995;Georgiou, Iansek, Bradshaw, Phillips, Mattingley, & Bradshaw, 1993;Jones, Phillips, Bradshaw, Iansek, & Bradshaw, 1992;Rafal et al, 1987) or (2) they were allowed to refer to a written version of the sequence they had to produce at all times during the experiment (Harrington & Haaland, 1991). In this study, however, the subjects were unaware that the triads in the Practiced condition were made of the consecutive juxtaposition of the simple figures they had practiced in Phase III, nor that the triads in the Unpracticed condition were composed of novel simple figures that they had never traced individually before.…”
Section: Mirror-tracing Task: Integration Of Practiced Movementsmentioning
confidence: 99%
“…Third, evidence from animal (Brotchie, Iansek, & Horne, 1991a, 1991b, clinical (Doyon et al, 1997a(Doyon et al, , 1998Georgiou et al, 1994Georgiou et al, , 1995Georgiou et al, , 1993, and neuroimaging investigations (Doyon et al, 1997b(Doyon et al, , 1996bGrafton et al, 1994;Jenkins et al, 1994;Seitz, Roland, Bohm, Greitz, & Stone-Elander, 1990) has demonstrated that the striatum is critically involved in the late phases of learning where automatization of a skill is thought to occur. Consistent with such a notion is the absence of deficit observed in both PD groups that may result from the fact that, in the present study, subjects had not achieved automatization of the task.…”
Section: Mirror-tracing Task: Integration Of Practiced Movementsmentioning
confidence: 99%
“…A number of studies have suggested that patients perform movements that are guided by external cues more easily than self-initiated movements (Flowers, 1976;Cools et al, 1984;Robertson and Flowers, 1990;Georgiou et al, 1993). These observations are con sistent with theories of the cortical organization of move ment that distinguish between externally cued and inter nally generated movements (Wise, 1984;Goldberg, 1985;Passingham, 1987Passingham, , 1993.…”
Section: Introductionmentioning
confidence: 78%
“…More proprioceptive feedback may have been required to achieve balance because of disturbances. A feasible explanation for increased step time might be that longer preparation for the movement causes longer execution time [18].…”
Section: Effect Of Optic Flowmentioning
confidence: 99%